2021
DOI: 10.3340/jkns.2020.0054
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Stent-Assisted Coiling Using the Neuroform Atlas Stent in Unruptured Wide-Necked Intracranial Aneurysms

Abstract: Objective : Although stent-assisted coiling (SAC) has been reported to be safe and effective in treating wide-necked aneurysms, the technique has procedure-related complications. Thus, we reported our experiences of SAC using the Neuroform Atlas stent in treating wide-necked aneurysms and evaluated the incidence of and risk factors for procedure-related complications. Methods : From March 2018 to August 2019, we treated 130 unruptured wide-necked aneurysms in 123 patients with Neuroform Atlas stents. Angiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…This patient's vision recovery supports this hypothesis. Two previous studies of SAC using the Atlas stent for treatment of naïve aneurysms have reported thromboembolic complication rates of 3.8 and 2.3%, respectively, and hemorrhagic complication rates of 0.8 and 0.8%, respectively (33,34). Reported thromboembolic complication rates in SAC studies using the Neuroform and Enterprise (Codman Neurovascular, Raynham, MA, USA) stents were 8.8 and 8.7%, respectively (35,36).…”
Section: Discussionmentioning
confidence: 97%
“…This patient's vision recovery supports this hypothesis. Two previous studies of SAC using the Atlas stent for treatment of naïve aneurysms have reported thromboembolic complication rates of 3.8 and 2.3%, respectively, and hemorrhagic complication rates of 0.8 and 0.8%, respectively (33,34). Reported thromboembolic complication rates in SAC studies using the Neuroform and Enterprise (Codman Neurovascular, Raynham, MA, USA) stents were 8.8 and 8.7%, respectively (35,36).…”
Section: Discussionmentioning
confidence: 97%
“…The procedure-related major adverse events and thromboembolic complications were acceptable, and most of the literature showed very high rates of technical success (Table I) . However, a few cases were reported with suboptimal deployment in unexpected locations and stent migration during the procedure (2,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The suboptimal stent deployment occurred because of the microcatheter's sudden uncontrolled movement to the proximal part of the target artery during the opening and deployment of the stent.…”
Section: Discussionmentioning
confidence: 99%
“…Because unexpected microcatheter withdrawal occurs more frequently in tortuous vessels, physicians should be aware of this possibility when treating patients with complex vascular architecture using the catheter jailing technique. To avoid unexpected microcatheter movement and incorrect stent deployment, the stent should be deployed with appropriate tension of the push wire, careful unsheathing of the microcatheter, and verified firm landing of the distal stent end (10,11). To prevent the thromboembolic event, we maintain the dual antiplatelet regimen with aspirin (100 mg/day) and clopidogrel (75 mg/day) during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The deliverability through low-profile microcatheters and its open-cell design are the technical features that allow a safe Y-stenting procedure. A recent case series assessing the outcomes of stent-assisted coiling procedures using Neuroform Atlas stents provided promising results [ 10 , 16 , 17 , 28 ]. However, the number of reports on cases treated with Y-stent-assisted coiling and Neuroform Atlas stents is very limited [ 5 , 9 , 13 , 16 , 28 ].…”
Section: Introductionmentioning
confidence: 99%